(untitled) (Belas Infiéis, 2012)
The present study aims at promoting a reflection on the relevance of the Discourse Analysis for the Translation Studies based on the theories of the main researchers for both areas. To do so, this paper is divided into three sections. In the first section, we deal with Discourse Analysis theories based on Brown and Yule (1983); Fairclough (1992) and Hatim and Mason (1990). In the second section, we present some aspects of the theories related to Translation Studies. In the following section, we raise some reflections regarding the interface Discourse Analysis and Translation Studies according to the theories presented previously. Finally, we present the conclusions concerning the research carried out in this paper.